Gasifikasi Batubara dan Limbah Pertanian Guna Mendapatkan Bahan Bakar Gas Alternatif - Agus Nugroho; Joko Rochmadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
Now, along with the price of kerosene is expensive , hence the idea of the use of coal briquettes in ground water reappears . Even the government has planned to make coal briquette stove 10 million to help the poor who can not afford to buy kerosene . However, it is still lacking in the community response including the small and medium enterprises ( SMEs ) who are currently looking for confusion cheap fuel substitute for oil , coal briquettes because it still contains some weaknesses include air pollution , especially smell and smoke , in side need time ( 5-10 minutes, depending on the quality of the coal briquettes ) to lit it , after a great fire was lit a little difficult to manage. Gasification system has several advantages over direct combustion of coal . Because the form of gas, combustion gas through the gasification of coal is much more easily controlled than direct combustion of coal , gas coal gasification process results can be used for various purposes , among others, to cook , drive the gas turbine , motor fuel moving in , as fuel in boilers, as well as for lighting. Utilization of biomass gas for cooking purposes using a reactor or a device called a gasification furnace . However, for me - gasification of coal gasification furnace required a special design so that the process of gasification and combustion can take place more efficiently and more clean.